Improving Elementary School Students’ Science Literacy Skills Through Digital Picture Storybooks - Duta Arindya Naresti; Suratmi; Hartono (Jurnal Ilmiah Sekolah Dasar, 2024)
Science literacy skills are essential in 21st century learning because they allow individuals to effectively communicate knowledge and research results to the public. This research aims to develop a feasible, practical, and effective digital picture book in improving the science literacy skills of elementary school students. The research method used is research and development (R&D) with the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subject of the study is fourth grade students. Data collection techniques are carried out through interviews, product validation questionnaires, student response questionnaires, and science literacy ability tests. The data analysis used is quantitative descriptive. Product validation is carried out by material experts, media experts, linguists, and practitioners (teachers). The validation results show that the developed digital picture storybook is included in the very feasible category. From the results of one-to-one and small group trials, digital picture storybooks are categorized as very practical to use. Meanwhile, from the results of the field test, students' science literacy skills have increased with a moderate N-Gain level. Therefore, it can be concluded that the development of this digital picture story book has produced a digital picture book that is feasible, practical, and has a positive impact on improving the science literacy skills of elementary school students.